HUBUNGAN PEMAHAMAN MATERI FIQIH DENGAN PEMBENTUKAN KARAKTER KUJUJURAN SISWA SISWA DI SMK MUHAMMADIYAH 2 BOJA - Miftachul Khasanah; Syaiful Hadi (As-Sulthan Journal of Education, 2025)
This research aims to describe the role of fiqh teachers in improving the formation of students' honest character. Because apart from teaching fiqh subjects, fiqh teachers also have an important role in providing good role models for the development of dignified student character. This research uses qualitative. Data collection techniques, namely, observation, interviews and documentation. The results of the research show that the role of fiqh teachers is a driving factor in improving the character of students at SMK Muhammadiyah 02 Boja. In particular, teachers act as motivators to encourage learning activities. Apart from that, the fiqh teacher as a guide in the character development of students at SMK Muhammadiyah 02 Boja as a teacher must try to provide various information about religious culture that is needed in the fiqh teaching and learning process, evaluating the results of fiqh learning at each stage. religious cultural activities carried out and creating appropriate opportunities for each student to study jurisprudence according to their individual characteristics, and the role of the jurisprudence teacher as an initiator in improving the character of students at SMK Muhammadiyah 02 Boja, namely displaying learning media, using cellphones and practicing. All of this is done so that students understand the material presented.